Perbaikan Tingkat Risiko Musculoskeletal Disorders Berdasarkan Pendekatan Nordic Body Map dan Rapid Upper Limb Assessment Pada Hasil Rancang Bangun Mesin Roasting Kopi Digital Otomatis - Ratih Rahmahwati (Jurnal Rekayasa Sistem Industri, 2021)
The roasting process of coffee beans in West Kalimantan, especially Pontianak city, is still done traditionally. The coffee roasting process is done manually by using a fire stove as a heater. Workers with standing posture stir the coffee beans continuously, and it can take 4 hours for 20 kilos of coffee beans. Standing work posture is required for stirring the coffee beans but can cause fatigue in workers due to long-standing times and high heating temperatures. This situation causes the roasting process to be less efficient and can cause the roasting process to be uneven. The purpose of this study was to identify musculoskeletal complaints of standing work posture in the manual coffee roasting process and provide an evaluation of corrective work posture when using the design results of an automatic digital roasting machine. The methods used in this study were the Nordic Body Map (NBM) and the Rapid Upper Limb Assessment (RULA) to assess the level of risk of posture for musculoskeletal complaints. The results of the identification of body points that experience fatigue were carried out by distributing NBM questionnaires and evaluating the worker's posture using RULA on CATIA V5R20. Based on the existing NBM, the risk score is 78, and the final RULA score is 6, which means that immediate corrective action is needed because the work posture is categorized as dangerous and does not meet ergonomic principles. Improvement of working posture is made by designing a roasting machine that is digital and automatic. So the workers do not need to mix the coffee beans manually. Based on roasting machine implementation results, there was a significant change in the NBM score and the final RULA score. The NBM results obtained a score of 55 which means that the risk is moderate with the risk of fatigue in the neck, right leg and, left leg. Meanwhile, evaluation of work posture based on RULA on CATIA obtained a final score of 3, which means that the work posture is not dangerous and does not require immediate improvement.